ONLINE GAMBLING: WHAT IS IT AND HOW TO DEAL WITH IT? - Dewi Nurnindyah; Intan Pawestri Widiyanto; Shania Wilnirosanti Angeline (STTAL POSTGRADUATE - INTERNATIONAL CONFERENCE, 2024)
Indonesia has been declared an emergency to deal with online gambling, many people are caught in online gambling, from children to adults, so the government has formed a special Task Force for Online Gambling since 2023 to eradicate the problem of online gambling in Indonesia. Online gambling addiction behavior does not recognize race, age, gender and occupation, including state officials, one of whom is an Indonesian Navy soldier. There has been an increase in violations committed by Indonesian Navy soldiers regarding online gambling issues in recent years. The negative impacts resulting from online gambling addiction include causing the risk of suicide, worsening financial conditions for oneself and one's family, triggering criminal acts and endangering others, destroying relationships with family and other parties, and being trapped in a vicious circle with online loans. This article discusses the history of gambling in Indonesia, the meaning of online gambling, types of online gambling, explanations from a psychological perspective, influencing factors and how to prevent online gambling addiction. Therefore, online gambling addiction needs to be discussed from a psychological perspective because it is a behavioral disorder that causes many problems and must be eradicated immediately.